Red dragon (Hylocereus polyrhizus) fruit peel extract increased the motility and viability of spermatozoa of hypercholesterolemic rats (Rattus norvegicus) - Niken Meyliana Sari; M. Gandul Atik Yuliani; Eduardus Bimo Aksono Herupradoto; Nanik Hidayatik; Nurhusien Yimer; Tatik Hernawati (Universitas Airlangga, 2023)
This study aims to determine the effect of red dragon (Hylocereus polyrhizus) fruit peel extract (RDFPE) on spermatozoa motility and viability of hypercholesterolemic rats (Rattus norvegicus) as a model. Twenty male rats were randomly divided into negative control (NC), positive control (PC), treatment 1 (T1), treatment 2 (T2), and treatment 3 (T3) groups. All rats were given 2 mL of high cholesterol feed orally every day for 28 days. On day-15, all rats were measured for their blood cholesterol levels, followed by treatment for 14 days. Rats in the NC, PC, T1, T2, and T3 groups were treated with 1% Na-CMC, Simvastatin 10 mg/kg BW, and RDFPE of 500, 750, and 1000 mg/kg BW, respectively. On day-29, all rats were sacrificed to evaluate spermatozoa viability and motility. The results showed that spermatozoa viability and motility in the hypercholesterolemic rats (NC) group were the lowest (p <0.05) among the groups. Treatment of hypercholesterolemic rats with Simvastatin 10 mg/kg BW (PC) group showed higher (p <0.05) spermatozoa viability and motility compared to the NC group. RDFPE dose of 1000 mg/kg BW (T3 group) resulted in higher (p <0.05) spermatozoa viability and motility compared to other RDFPE doses (T1 and T2) and the control (NC) groups, and it was similar (p >0.05) compared with the Simvastatin treated (PC) group. It could be concluded that the administration of 1000 mg/kg BW ethanolic extract of red dragon fruit (Hylocereus polyrhizus) peel increased the viability and motility of spermatozoa of hypercholesterolemic rats (Rattus norvegicus) which were the same as the group of rats given Simvastatin 10 mg/kg BW.